Pengembangan Sistem Informasi Manajemen Pengelolaan Sampah Digital Kawasan Pantai Kalomang Kabupaten Kolaka: Development of Digital Waste Management Information System for Kalomang Beach Area, Kolaka Regency - Rasyid, Rasmiati; Ningsi, Nurfitria; Muchtar, Mutmainnah; Sarimuddin, Sarimuddin (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
Kalomang Beach is a famous tourist destination in Kolaka. Currently, waste management is carried out in a manner where the garbage pick-up process is carried out when the garbage is full and even pollutes this tourist area, this of course can lead to environmental damage and decreased visitor interest. This research seeks to identify critical issues in waste management at Kalomang Beach and provide an integrated waste management platform to assist the government in assessing waste activities and guidelines. The information provided by this system can improve public health on a local and global scale. The utilization of the SDLC System Development approach in this case the Waterfall method allows for a detailed and appropriate design which tends to be more measurable in terms of time and cost, the use of data modeling through the Unified Modeling Language, and blackbox testing shows that the waste input form is in accordance with the needs of the user where it places groupings of waste types that make it easier for tourist area officers to report the availability of waste that is ready to be picked up. Future system development is important to consider aspects of sustainability, user training, and integration with IOT or microcontroller based waste monitoring systems.   Keywords— Integrated Waste Management Information System, Kalomang Beach, Waterfall